Preliminary Neuropsychological Normative Data in a Healthy Sample of Puerto Rican Women. (30th August 2019) - Rodriguez-Benitez, R J; Muriel, F; Rivera-Aviles, A; Matos, M; Wojna, V
Abstract: Objective: Accurate diagnosis of neuropsychological (NP) impairment in Spanish-speaking Latinx women is limited by a lack of appropriate norms. While multiple normative datasets have emerged for Mexican/Mexican-American populations, there is a particular dearth of normative options for Puerto Rican women. This study collected normative data in a sample of Spanish-speaking healthy women in Puerto Rico (PR). Participants and Method: The sample consisted of 63 healthy, HIV-seronegative women recruited as comparison participants in a longitudinal HIV-seropositive Latinx Women Cohort study at the University of Puerto Rico during 2002-2017. The NP battery included measures from seven cognitive domains: verbal fluency, executive functioning, processing speed, learning, memory, sensory, perceptual, and motor skills. Results: The sample's age ranged from 20-77 years (M = 42.14; SD = 12.71) and education ranged from 9-18 years (M = 13.74; SD = 2.09). The NP test M and SD raw score results were: Trail Making A (M = 41.29; SD = 14.87), Trail Making B (M = 105.14; SD = 49.77), Grooved Pegs Dominant Hand (M = 78.49; SD = 31.91), Stroop Word/Color (M = 47.86; SD = 23.66), Rey Verbal Learning Test Total (M = 42.0; SD = 9.36), Verbal Fluency FAS-F (M = 11.27; SD = 4.20), FAS-A (M = 12.05; SD=4.34), FAS-S (M = 10.67; SD = 4.19), Digit Span (M = 12.16; SD = 3.28), Spatial Span (M = 10.95; SD = 3.62), Benton Judgment of Line Orientation Test (M = 18.10; SD = 5.54), Finger Tapping Left (M = 50.58; SD = 7.78), Finger Tapping Right (M = 53.87; SD = 8.83), Seashore Rhythm Test (M = 23.38; SD = 3.99), and Rey Complex Figure Test Immediate (M = 13.17; SD = 6.99) and Delay (M = 13.58; SD = 7.21). The NP norms were stratified by age (10-year increments and 60+) and education (< 12 years and 12+ years). Conclusions: This preliminary study provides initial normative data from a sample of healthy women living in PR, which can improve NP diagnostic accuracy for this population. This is particularly important given that this population experiences worse health outcomes compared to other Latinx subpopulations.